Do institutional quality and financial development affect sustainable economic growth? Evidence from South Asian countries - Farhan Ahmed; Shazia Kousar; Amber Pervaiz; Aiza Shabbir (Borsa Istanbul Review, 2022)
Institutional quality and financial development are important pillars of sustainable economic growth; this study explains the role of institutional quality and financial development in green growth in the South Asian economies over the period 2000–2018 with data from the World Bank. This study examines long-run cointegration among the variables modeled using the cointegration techniques by Pedroni, Kao, and Westerlund. Our results of panel cointegration approaches reveal long-run cointegration between financial developments, institutional quality, and green growth. Further, the study employs fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) to examine the role of institutional quality and financial development in green growth in the long run. Our findings reveal that institutional quality and financial development are driving factors in promoting green economic growth in the long run. This paper shows the important policy implications of promoting green growth in the South Asian economies.